Constitutional Court Verdict on "Error In Objecto" Lawsuit in Dispute Over Regional Election Results - Rahmawati, Nurlaili; Nugraha, Sigit Nurhadi (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2022)
Abstract:  The settlement of cases resulting from the Regional Head Election (Pilkada) is still within the authority of the Constitutional Court. In deciding this case, the Constitutional Court made explicit regulations regarding the procedural law of the trial as outlined in the Constitutional Court Regulations. One of the problems that arise in the examination (trial) of disputes over the results of the regional elections is that the application submitted by the losing party (applicant) turns out to be the wrong object (error in objecto). This error usually occurs because the object being sued is not the final decision on the election results. This research is a normative juridical research that aims to examine the attitudes and decisions of the Constitutional Court regarding requests for disputes over Regional Head Elections (Pilkada) that are Error In Objecto. The result of this study is that the Plaintiff in making the application must clearly not be mistaken in determining the object. In the case/dispute over the results of the regional elections, the object of the lawsuit is the final decree of the General Elections Commission regarding the determination of the results of the election results and not others. Accuracy in making posita and petitum is very important because wrong posita and petitum will lead to the wrong and fatal determination of the object of the application. When this is the issue, the Constitutional Court will not accept the application because it is not authorized. An error in determining the object of this application in procedural law is termed error in objecto, so accuracy as an applicant, respondent, or related party is needed. The recommendation given is that the plaintiff should be more careful in making applications and the revision of the application given by the Constitutional Court at the preliminary hearing, can be used by the applicant to correct his application so as not to incorrectly determine the object of the application/error in objecto.